Bibliometric and content analysis on emerging technologies of hydrogen production using microbial electrolysis cells. (27th November 2020) - Zhao, Na; Liang, Dawei; Meng, Shujuan; Li, Xiaohu
Abstract: Microbial electrolysis cell (MEC) is a promising and significant approach for hydrogen production, owing to the low energy consumption and high yield/recovery efficiency. In this review, bibliometric analysis has been conducted on current research trends of MECs, followed by the content analysis of the direction and strategy for improving the hydrogen production to enlarge MECs' applicability. Results show that energy concerns are the primary focus in MEC studies, and particular attention has been paid to decreasing internal resistance and hydrogen diffusion that may be crucial for the improvement of the yield of hydrogen production and recovery. Moreover, this study particularly reviews the development of the cathode catalysts and explores the applicability of different MEC configurations, including single-and two-chamber MECs with different kind of membranes. It also identifies the potential advantages of porous membranes as a separator in MECs and discusses the porous membrane, in conjunction with advancing hydrogen-harvesting approaches, is crucial for the improvement of hydrogen production. Finally, capital cost of MECs has been necessarily discussed, which would be significant, valuable, and beneficial to the academic research and the industrial community. Highlights: Bibliometric analysis shows the current trends of H2 production in MECs. Content analysis shows the direction and strategy for improving H2 production. This review summarizes the research of cathode catalysts, configurations and costs. Decreasing internal resistance and H2 diffusion is crucial to enhance H2 recovery. This study identifies the advantages of porous membranes as a separator in MECs.